Research Gap on Lean-Green Integrated Approaches and Its Impact on Sustainability Performance: A Post COVID-19 Reminiscence - Bilal Hassan; Urooj Pasha (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study is not about the evolution of Lean or Green Practices but the latest developments of its integration in positive and negative ways and their main classification, benefits, and limitations. We critically assess previous research from various theoretical perspectives in the lean-green domain. Review is conducted after the COVID-19 pandemic. It guides significant awareness related to ecological and environmental issues helping the organizations, governments, and other stakeholders in economic recovery and environmental security and the conservation of natural resources. We use the five-criteria approach for conducting the literature review. Time chosen for this systematic literature review is 2010 to 2021. 61 research articles used to analyze and explore the impact of integrated lean-green concepts and ultimately its results on triple bottom line (TBL) performance of the organizations. Comprehensive results show that integrated lean-green approaches have significant impact on a firm's sustainability performance, although few research studies have negative results and related trade-offs as well. Findings and conclusions are beneficial for researchers, organizations, governments, and other stakeholders because this paper has the critical and comprehensive explanation of different classifications, theoretical perspectives, benefits, limitations, and related future directions of lean-green integration. As this study is conducted after the COVID-19 pandemic, this review guides significant awareness related to the environment for economic recovery and environmental security as well as the conservation of natural resources.